Effect of International CPO Prices, Substitution Goods Prices, and Exchange Rates on Crude Palm Oil (CPO) Export Volume in Indonesia - Yanira Berthi Ayu Pradina; Dhian Adhitya (Jurnal Ekonomi Pembangunan, 2023)
This study aims to analyze the effect of international CPO prices, substitution goods prices, and exchange rates on CPO export volume in Indonesia in the long and short term. The type of research used is quantitative. The data used in this study used secondary data in the form of time series data from January 2014 to June 2022. The data was obtained from the websites of Bank Indonesia (BI), the Indonesian Central Statistics Agency (BPS), the Ministry of Trade and Economic Research. The analysis method used in this study is the Error Correction Model (ECM). The results of research that has been conducted where international CPO prices in the short and long term have a significant and positive influence on Indonesia's CPO export volume. Meanwhile, the price of substitution goods in the short and long term has a negative relationship with CPO Export Volume. Then the variable exchange rate in the long term and in the short term has a significant influence on the CPO Export Volume. For this reason, the government is that it can be used for information and input materials to improve CPO exports for the better in the future. This can be done in several ways to reduce export costs charged to producers so as to maximize international CPO prices in Indonesia.